The detention of the suspect as an investigative action (Journal of actual problems of jurisprudence, 2018)
Based on scientific articles that the detention of the suspect, the rights of the suspect, the procedure and conditions of detention of persons detained on suspicion of committing a crime, and the criminal procedural coercive measures, on the procedure of detention of persons detained as suspects. In given article are considered causes of detention of suspect as a emergency measure of procedural enforcement, which employed by state body of inquiry, prosecutor or interrogator, also phases procedural order of arrest.State enforcement is diverse by own character and employment aim. Community relations diversity and impinge provides nessecity of state enforcement diverse kinds employment, which have strict distinction by own content, cause and order of realization. It can appear for not just measures of criminal-law, civil-law, administrative-law, disciplinary-law effect. Diversity of state enforcement is criminal-procedural enforcement, that present complex all measures of enforcement which were provided by criminal-procedural norms.Kew words: suspect, suspect’s detention, procedural order, preventive measures, procedural enforcement measures.